1954
DOI: 10.1002/j.1537-2197.1954.tb14396.x
|View full text |Cite
|
Sign up to set email alerts
|

Maize Endosperm Tissue Grown in Vitro I. Culture Requirements

Abstract: IN RECENT YEARS the number of plant tissue cultures grown in vitro has been greatly increased. Other than the usual callus cultures derived from dicotyledonous plants (Gautheret, 1947a), tissues derived from monocotyledonous plants as well as from the Pinaceae, Ginkgoaceae, Filicinae, and the Lycopodinae have been established in culture. Curtis and Nichol (1947), obtained cultures of overgrowths produced by orchid embryos grown in vitro. Morel and Wetmore (1951a) were successful in growing callus tissues deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1954
1954
1993
1993

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…As can be seen from the data in table I, the opposite growth effects are attributed to glucose and sucrose for these endosperm cultures. The same relative effectiveness of these sugars in the support of growth for endosperm cultures of a different variety of maize holds true (15). Increases in concentration of sucrose in the medium from 0.05 M to 0.2 M result in slight increases in pigment content.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…As can be seen from the data in table I, the opposite growth effects are attributed to glucose and sucrose for these endosperm cultures. The same relative effectiveness of these sugars in the support of growth for endosperm cultures of a different variety of maize holds true (15). Increases in concentration of sucrose in the medium from 0.05 M to 0.2 M result in slight increases in pigment content.…”
Section: Resultsmentioning
confidence: 73%
“…The endosperm tissue cultures were isolated from the maize variety, 'Black Mexican Sweet', according to the methods described by Straus and LaRue (15). The nutrient medium contained White's major elements, Nitsch's trace elements (6), 0.5 % Seitzfiltered yeast extract, 2 % sucrose, and 0.9 % agar unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that asparagine at a concentration of 1.5 X 10-2 M added to the basal mineral-sugarvitamin medium supported better growth than either yeast extract or casein hydrolyzate. Details of the development of this synthetic medium are being published elsewhere (8).…”
Section: Methodsmentioning
confidence: 99%
“…However, one area of investigation that has received little attention is carbohydrate utilization in vitro. Straus and LaRue (1954) first investigated the effects of various carbohydrates on the growth of maize endosperm cultures and determined that Suc was most effective in supporting growth of maize endosperm cultures. Since this early study, very little has been reported relative to altemative carbon sources in the culture of monocots, with the distinct exception of severa1 reports on carbon utilization in cultures of sugarcane.…”
mentioning
confidence: 99%